Smart Pop Up Book Sebagai Penunjang Literasi Siswa di Madrasah Ibtidaiyah - Laela, Siti Nur; Sholihah, Mar’atus (Bidayatuna, 2024)
Literacy is the main pillar in the world of education.. Literacy problems experienced by MI Assunniyyah 45 Paseban students, out of a total of 115 students, there were 33 students whose literacy was still low. In increasing literacy, there is a need for learning media to support students for successful learning, the media used are:Smart Pop Up Book. The focus of this research is as follows: Learning media Smart Pop Up Book as supporting students' reading and writing literacy at Madrasah Ibtidaiyah. The type of research used is qualitative research with a descriptive approach. Data collection techniques through observation, interviews and documentation. The research location was at MI Assunniyyah 45 Paseban for approximately three months from March to May 2024. The research subjects were the school principal, first and second grade teachers and students. Based on the research results, it shows that by using mediaSmart Pop Up Book as supporting student literacy at Madrasah Ibtidaiyah, students are very enthusiastic about learning, during the learning process students do not feel bored, students feel happy reading through Pop Up Book so that some students who were previously still spelling have started to become fluent, writing becomes more neat and thorough.